Optimization Design of Brake Disc Structure for Brake Squeal Suppression - Pan Gongyu; Liu Zhikang; Xu Qizhao; Chen Lin (Jixie chuandong)
Aiming at the problem of brake squeal of automobile disc brake, a method based on weighted brake squeal tendency coefficient is proposed to evaluate the brake squeal performance. On the basis of establishing a complex mode finite element model of the disc brake, the validity of the model is verified by the noise bench test. By combining the central composite test design, Response Surface Method （RSM） surrogate model method and the Pointer optimization algorithm, and taking the minimum weighted brake squeal tendency coefficient as the optimization goal, the structural optimization design is carried out for the unilateral disc height, heat sink rib height, elastic modulus and disc cap height of the brake disc. The results show that the optimization design method proposed can significantly improve the efficiency of the optimization solution, effectively reduce the squeal tendency of the disc brake in the full frequency band, and suppress the generation of brake squeal noise.